An Assessment of Room Acoustics Performance of Baiturrahman Grand Mosque - Laina Hilma Sari; Zulfian Zulfian (Faculty of Science and Technology Universitas Islam Negeri Ar-Raniry, 2020)
Abstract : Acoustical design as part of the audio comfort influences the architectural design strategy of a mosque significantly. As belonging to the speech room criteria, a mosque should meet some acoustic room requirements to deliver the solemnness to the worshipper during the prayer. Concerning this, the study aims to assess the indoor acoustics performance of Baiturrahman Grand Mosque, Banda Aceh. Baiturrahman grand mosque is an important place of worship for Acehnese and becoming a landmark of Banda Aceh City. The mosque which contains a lot of history of Aceh was built in heavy construction, i.e. concrete wall, marble coated floor, and concrete dome ceiling. Due to its significance, the room acoustics of the mosque as the primary design considerations in a speech room type is evaluated. The acoustics parameters estimated are Noise Criteria (NC), Sound Pressure Level (SPL), Reverberation Time (RT), and Rapid Speech Transmission Index (RASTI). The background noise was recorded for delivering the noise criteria and being the primary data carried out in the acoustic simulation. The study utilised CATT-Acoustic v7.2 software for simulating predicting SPL, RT, and RASTI.Abstrak : Desain akustik merupakan bagian dari parameter audio yang mempengaruhi desain arsitektur masjid secara signifikan. Masjid termasuk dalam kategori speech room yang harus memenuhi beberapa persyaratan akustik ruang untuk dapat menghadirkan kekhusyukan kepada jamaah selama sholat. Penelitian ini bertujuan untuk menilai kinerja akustik dalam ruangan Masjid Raya Baiturrahman, Banda Aceh. Masjid Raya Baiturrahman adalah tempat ibadah yang penting bagi orang Aceh dan menjadi simbol Kota Banda Aceh. Masjid yang memuat banyak sejarah Aceh ini terbuat dari dinding beton, lantai berlapis marmer, dan langit-langit kubah beton. Pada studi ini, parameter akustik ruang yang dievaluasi adalah Kriteria Kebisingan (NC), Tingkat Tekanan Suara (SPL), Waktu Gema (RT), dan Indeks Transmisi kecepatan Bicara (RASTI). Kebisingan latar belakang direkam untuk memberikan kriteria kebisingan dan menjadi data primer yang dilakukan dalam simulasi akustik. Studi ini menggunakan perangkat lunak CATT-Acoustic v7.2 untuk mensimulasikan prediksi SPL, RT, dan RASTI.